Implementasi Sistem Akuntansi Berbasis Akrual Pada Kantor Kementerian Agama Kabupaten Jepara - Fatchur Rohman; Aizatul Muniroh (Jurnal Rekognisi Akuntansi, 2018)
This research aims to know and evaluate the extent to which the implementation of accrual-based accounting system at the Office of the Ministry of religion (KEMENAG) District of Jepara Year 2018. The formula in this study into how the implementation of accrual-based accounting system at the Office of the Ministry of Religion Jepara Regency year of 2018. This research is located in the Office of the Ministry of Religion with the kind of Jepara Regency qualitative research. The source of the data used in this study i.e., primary data and secondary data. Method of data collection in this study use techniques of observation, interviews, and documentation. The results of this research show that the religious Ministry Office reporting Jepara Regency is in compliance with the Government Regulation Number 71-year 2010 On Accrual-based Government accounting standards. This is supported by the existence of real evidence that Kemenag Jepara Regency has been enthusiastically implement and optimize the accrual-based accounting system in improving the quality of reporting as investigators get in field and supported the budget details have been in make to use of those systems.